Aperture coupling rectangular slotted circular ring microstrip patch antenna - Abil Fathir Majid; Yulisdin Mukhlis (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper designed circular ring microstrip patch antenna using aperture coupling feeding techniques with rectangular slots on the patch for LTE. The use of aperture coupling feeding techniques were expected to optimize antenna parameters performance. The addition of rectangular slots on the patch produced multi resonant frequencies than the original characteristics. The simulated optimized design generated 1.8 GHz, 2.1 GHz, and 2.72 GHz with Return Loss value -22.3683 dB, -18.8133 dB, -24.3451 dB and VSWR value 1.1648, 1.259, 1.1291. Meanwhile, the measurement results of fabricated antenna showed the frequency produced by the antenna was 1.8 GHz with value of Return Loss and VSWR -18.257 dB and 1.278 in a reference value of VSWR < 2 and Return Loss < -10 dB.